IMPLEMENTATION OF THE PRINCIPAL'S MANAGERIAL FUNCTION IN IMPROVING NON-ACADEMIC STUDENT ACHIEVEMENT IN ELEMENTARY SCHOOLS - Mundrikah, Siti; Senowarsito, Senowarsito; Maryanto, Maryanto (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
This study describes the implementation of the principal's managerial function in improving students' non-academic achievement at SD Negeri 07 Purwoharjo. A qualitative approach with a case study design was used in the study. Data were obtained through interviews, participatory observation, and documentation of respondents. Respondents consisted of the principal, extracurricular teachers, committees, and parents. Data were analyzed using the Miles and Huberman interactive model. The results showed that the implementation of the principal's managerial function was effective and collaborative, encompassing four stages: planning, organizing, implementing, and monitoring. The principal acted as a participatory leader and was able to organize all elements of the school in managing non-academic activities. The increase in non-academic achievement occurred due to strong cooperation and synergy between the principal, teachers, committees, and parents in creating a positive culture and character. The findings of this study emphasize that the effectiveness of the principal's leadership is influenced by the ability to combine managerial values ​​with socio-cultural conditions in the school.